Global sharing, local innovation: Four schools, four countries, one curriculum. (1st December 2016) - Castelo-Branco, Luís; Finucane, Paul; Marvão, Pedro; McCrorie, Peter; Ponte, José; Worley, Paul
Abstract: Background: Many internal and external obstacles, must be overcome when establishing a new medical school, or when radically revising an existing medical curriculum. Aims: Twenty-five years after the Flinders University curriculum was introduced as the first graduate-entry medical programme (GEMP) in Australia, we aim at describing how it has been adopted and adapted by several other schools, in Australia and in Europe (UK, Ireland, and Portugal). Method/Results: This paper reports on the experience of four schools establishing a new medical school or new curriculum at different times and in different settings. Conclusions: We believe that these experiences might be of interest to others contemplating a similar development.